Effects of size and phase of TiO2 in poly (vinyl alcohol)-based gel electrolyte on energy storage ability of flexible capacitive supercapacitors. (1st August 2022) - Kuo, Tsung-Rong; Lin, Lu-Yin; Lin, Kuan-Yu; Yougbaré, Sibidou
Abstract: Flexible supercapacitor (FSC) with high power density and cycle life has been considered as efficient energy storage device for soft electronics. Gel electrolyte is used in FSC to avoid electrolyte leakage. Titanium dioxide (TiO2 ) with high dielectric constant and abundant surface vacant sites is regarded as efficient inorganic filler in gel electrolyte. In this work, TiO2 nanoparticles are incorporated in polyvinyl alcohol/H3 PO4 gel electrolyte for FSC. Different particle sizes and phases of TiO2 are firstly used as inorganic filler in gel electrolyte to enhance ionic conductivity via reducing crystallinity of polymer. The FSC with P25 TiO2 in gel electrolyte presents the best energy storage ability due to the smallest particle size and preferable phases. The highest specific capacitance (CF ) of 69.2 F/g at 20 mV/s is obtained for FSC with optimized P25 TiO2 amount in gel-electrolyte. This FSC also shows the maximum energy density of 5.9 Wh/kg at 300 W/kg, and CF retention of 94% after 3500 charging/discharging cycles. This work demonstrates feasibility of TiO2 as efficient filler in gel electrolyte. It is worthy to study the relation between intrinsic property of TiO2 and energy storage ability of FSC in other gel-electrolyte systems. Graphical abstract: Unlabelled Image Highlights: TiO2 particles are added in polyvinyl alcohol/H3 PO4 electrolyte of supercapacitor. Various TiO2 sizes and phases are firstly used as inorganic filler in electrolyte. TiO2 filler is used to reduce polymer crystallinity and enhance ionic conductivity. Specific capacitance of 69.2 F/g (20 mV/s) is got for SC with optimal TiO2 amount. Supercapacitor shows a specific capacitance retention of 94% after 3500 cycles.